Physico-chemical comparison of Four commercially available mineral trioxide aggregates = Comparación fisicoquímica de cuatro mineral trióxido agregados disponibles comercialmente - Montero Aguilar, Mauricio 1978-
To compare the physicochemical composition of 4 MTAs commercially available in Latin America. ProRoot MTA (Dentsply, USA), MTA Angelus (Angelus, Brazil), MTA Flow (Ultradent, USA), and MTA Viarden (Viarden, Mexico) were physically and chemically compared. Scanning electron microscopy (SEM) images were obtained from the MTA powder and the prepared presentations. Energy Dispersive X-Ray Spectroscopy (EDS) analyses were performed by triplicate, to calculate the mass proportion of calcium (Ca), silicon (Si), the Ca/Si proportion among the 4 brands. Thermogravimetric analyses (TGA) were conducted (50ºC-1000ºC), and mass loss and inflection points were calculated for each material. Statistical differences for Ca and Si content were determined by ANOVA (p<0.05). SEM images showed evident differences in the appearance of both the powder and the prepared MTAs among brands. Angelus MTA showed cubic prisms not observed in the other 3 brands. ProRoot MTA and MTA Flow showed similar homogeneous structures. MTA Viarden was the less homogeneous, with random structures (>15um). When comparing the mass proportions of Ca and Si between the 4 powder samples, MTA Viarden showed a significantly lower proportions of both elements when compared with the other brands (p<0.005). TGA analysis showed a similar behavior for ProRoot MTA, MTA Angelus and MTA Flow, with less than 2% mass loss when the 1000C temperature was reached. MTA Viarden showed a mass loss of 9,94% before the 700C, indicating the presence of different content sensible to temperature degradation. The analyzed MTAs demonstrated to vary significantly in their chemical composition and physical characteristics. Clinicians must be aware of the differences between different brands of a same material, and future research should focus on the clinical implications of these differences.